Effect of heating on properties of some soils from Southern Nigeria and growth of rice - Kang, B.T.; Sajjapongse, A. (1980)
The effect of heating on the properties of Apomu (Psammentic Usthorthent), Egbeda (Oxic Paleustalf) and Gambari (Typic Plinthustalf) surface soils were studied under laboratory conditions. Heating at low temperatures (≤100°C) have no detrimental effects on soil properties, on the contrary it increased the soil extractable P, Mg, Fe, Mn and Zn levels. Pronounced reductions in total N, Org. C, Org. P and extractable Ca and Mg levels and marked increases in extractable P, Zn, Mn and Fe were observed by heating to 200°C. Heating to ≥500° had an adverse effect on soil chemical and physical properties. Plant height and dry matter yeild of rice plants were higher when grown on Egbeda soil previously heated to 100°C. With addition of N, P and K there was no observed beneficial effect of the heating treatment. Rice plants grown on Egbeda soil previously heated to 200°C showed high uptake of Mn. Plants grew badly in soil previously heated to 500°C.